1992
DOI: 10.1126/science.1553545
|View full text |Cite
|
Sign up to set email alerts
|

Biological Significance of Unwinding Capability of Nuclear Matrix-Associating DNAs

Abstract: Matrix attachment regions (MARs) are thought to separate chromatin into topologically constrained loop domains. A MAR located 5' of the human beta-interferon gene becomes stably base-unpaired under superhelical strain, as do the MARs flanking the immunoglobulin heavy chain gene enhancer; in both cases a nucleation site exists for DNA unwinding. Concatemerized oligonucleotides containing the unwinding nucleation site exhibited a strong affinity for the nuclear scaffold and augmented SV40 promoter activity in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
342
0
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(354 citation statements)
references
References 38 publications
9
342
0
3
Order By: Relevance
“…We have identified A-box and T-box motifs (54), the yeast ARS consensus sequence (55), the consensus sequence for Drosophila topoisomerase II (7,73), the base unpairing region (BUR) (4,5,63,64), the MAR recognition sequence (MRS) (44), origin of replication and homeotic protein recognition motifs (ORI), TG-rich sequences, curved DNA motifs, and kinked DNA motifs (56,57,65,66,68). The frequency of occurrence of these motifs in each MAR is listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified A-box and T-box motifs (54), the yeast ARS consensus sequence (55), the consensus sequence for Drosophila topoisomerase II (7,73), the base unpairing region (BUR) (4,5,63,64), the MAR recognition sequence (MRS) (44), origin of replication and homeotic protein recognition motifs (ORI), TG-rich sequences, curved DNA motifs, and kinked DNA motifs (56,57,65,66,68). The frequency of occurrence of these motifs in each MAR is listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…DNA sequences that bestow a propensity for bending have been associated with MARs (62). A role for unwinding potential as a defining element for MARs has been suggested by Bode and co-workers (63). These workers have used a 9 bp sequence, the base-unpairing region (BUR), as a preliminary indicator of unwinding potential, but in collaboration with Benham (64) they have devised a much more sophisticated method of predicting stress-induced unwinding.…”
mentioning
confidence: 99%
“…AT-rich sequences have been shown to possess strong nucleotide-unpairing properties [83], which may be involved in unzipping the DNA double helix during transcription initiation [84,85]. During eukaryotic interphase, chromosomes are organized into looped domains which are anchored to the nuclear matrix through DNA regions called matrix-attachment regions (MARs) [19,86].…”
Section: Classical Silencers (Silencer Elements)mentioning
confidence: 99%
“…Recently, a small circular vector named pEPI-1 has been developed that is unique in that it can function as a stable episome without coding for any protein of viral origin. 16 This vector contains a chromosomal scaffold/matrix attachment region (S/MAR) deriving from the 5 0 -region of the human interferon b-gene, 17 as well as the origin of replication of the simian virus 40 genome (SV40 ori), the GFP cDNA driven by the CMV immediate-early promoter and the gene conferring resistance to neomycin. By transfer of pEPI-1 into CHO cells, it was shown that this vector replicates episomally over many cell generations in the absence of large T antigen.…”
Section: Introductionmentioning
confidence: 99%